The Liberator : One World War II Soldier's 500-Day Odyssey From the Beaches of Sicily to the Gates of Dachau - Kershaw, Alex (New York Crown, 2013)
The Liberator is a story for the ages, an intensely human and dramatic account of one of history's greatest warriors and his unheralded role in America's finest achievement - the defeat of Nazi Germany
Include Illustrations, Maps, Bibliography and Index
Keywords: Military campaigns -- World War, 1939-1945 -- Campaigns -- Western Front -- United States. Army -- Officers -- Biography